2019
DOI: 10.1093/eep/dvz009
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific changes in Srebf1 and Srebf2 expression and DNA methylation with perinatal phthalate exposure

Abstract: Perinatal exposure to endocrine disrupting chemicals negatively impacts health, but the mechanism by which such toxicants damage long-term reproductive and metabolic function is unknown. Lipid metabolism plays a pivotal role in steroid hormone synthesis as well as energy utilization and storage; thus, aberrant lipid regulation may contribute to phthalate-driven health impairments. In order to test this hypothesis, we specifically examined epigenetic disruptions in lipid metabolism pathways after perinatal phth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Lipid metabolism is important for synthesis of steroid hormones and phthalate-driven aberrant lipid metabolism disrupts the normal metabolic and reproductive processes (Moody et al, 2019). In this study (Moody et al, 2019), it was demonstrated that when pregnant Long-Evans rats were administered mixture of phthalates 0 (CON), 200 (LO), or 1,000 (HI) mg/kg body weight/day during the perinatal period-the male offspring for both groups at PND90 had higher body weights than control. Sterol regulatory element binding proteins (SREBPs) have been hypothesized to play a pivotal role in phthalate-induced metabolic dysregulation (Johnson et al, 2011;Zhang et al, 2017).…”
Section: Lipid Metabolismmentioning
confidence: 80%
See 1 more Smart Citation
“…Lipid metabolism is important for synthesis of steroid hormones and phthalate-driven aberrant lipid metabolism disrupts the normal metabolic and reproductive processes (Moody et al, 2019). In this study (Moody et al, 2019), it was demonstrated that when pregnant Long-Evans rats were administered mixture of phthalates 0 (CON), 200 (LO), or 1,000 (HI) mg/kg body weight/day during the perinatal period-the male offspring for both groups at PND90 had higher body weights than control. Sterol regulatory element binding proteins (SREBPs) have been hypothesized to play a pivotal role in phthalate-induced metabolic dysregulation (Johnson et al, 2011;Zhang et al, 2017).…”
Section: Lipid Metabolismmentioning
confidence: 80%
“…DNA methylation was increased at two loci in testis of HI rats and reduced at another site surrounding Srebf1 transcription start site. Simultaneously, in rats belonging to the HI phthalate dosage group-in the adipose tissue increased DNA methylation at one region was observed within the first intron of Srebf2 (Moody et al, 2019). Thus, phthalate exposure impairs metabolism of lipids by DNA methylation through tissue-specific changes in gene expression.…”
Section: Lipid Metabolismmentioning
confidence: 95%
“…It also was indicated that vitamin D metabolite 25‐hydroxyvitamin D could induce SREBP protein degradation (33). Another study showed that VDR could directly bind to and control SREBF1 expression (8). SREBF1 as a transcriptor factor controls the start of the transcriptional cascade during adipogenesis, possibly through the serine/threonine‐protein kinase mTORC1 pathway (34).…”
Section: Discussionmentioning
confidence: 99%
“…Sterol regulatory element‐binding transcription factor 1 (SREBF1) can initiate the adipogenic transcriptional cascade and control the synthesis of cholesterol, fatty acid, triacylglycerol, and phospholipid (7). VDR can bind to and negatively downregulate SREBF1 (8). Evidence demonstrates that vitamin D deficiency can decrease VDR and increase serum cholesterol (9).…”
Section: Introductionmentioning
confidence: 99%